Genetic Evidence for Causal Effects of Immune Cell Subtypes on Postherpetic Neuralgia - Chen T; Tang S; Chen R; Ding W; Chen Y; Jian Z; Wu M; Jia M; Zhang X (Journal of Pain Research)
Taichang Chen,1,* Songjiang Tang,1,* Rong Chen,1 Wei Ding,2 Ying Chen,1 Zhonglu Jian,1 Min Wu,3 Min Jia,4 Xiuyi Zhang5 1Department of Anesthesiology, First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, People’s Republic of China; 2Department of Urology, First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, People’s Republic of China; 3The First Clinical School of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, People’s Republic of China; 4Department of Dermatology, First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, People’s Republic of China; 5Anesthesiology Department of Qiandongnan Traditional Chinese Medicine Hospital, Kaili, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Taichang Chen; Xiuyi Zhang, Email chentaichang227@gzy.edu.cn; 1525126342@qq.comBackground: Recent evidence indicates that immune cells are crucial in modulating the pathogenesis of postherpetic neuralgia (PHN), with significant associations identified between immune responses and the development of PHN. However, the specific dynamic immune profile, the underlying molecular mechanisms, and especially the causal relationship between immune cells and PHN have yet to be comprehensively elucidated.Methods: We implemented a comprehensive analytical framework incorporating two-sample Mendelian randomization (MR), multivariable Mendelian randomization(MVMR), and colocalization analyses to elucidate the causal relationships between immune cell phenotypes and PHN. Utilizing publicly available genetic datasets, we explored potential causal associations between 731 immune cell phenotypes and susceptibility to PHN. Comprehensive sensitivity analyses were performed to assess the robustness of the findings, evaluate heterogeneity, and investigate horizontal pleiotropy.The Steiger directionality test was utilized to address and reduce the likelihood of reverse causation.Results: After applying the Bonferroni-adjusted, eight immune cell phenotypes exhibited significant causal associations with PHN. Further MVMR analysis revealed a significant positive causal relationship between CD27 on IgD- CD38dim B cell and the risk of PHN, with an odds ratio (OR) of 1.228 (95% confidence interval [CI]: 1.059– 1.566, P = 0.011). Colocalization analysis offered limited evidence supporting a shared genetic architecture.Conclusion: Our findings present compelling genetic evidence that identifies CD27 on IgD- CD38dim B cell as a potential therapeutic target for the prevention and treatment of PHN. This study reinforces the mechanistic connection between immune cell function and the pathogenesis of PHN, highlighting the necessity for further exploration in this area. These insights provide significant guidance for future clinical research and the development of therapeutic strategies.Keywords: postherpetic neuralgia, causal relationships, colocalization analysis, MVMR, immune cells, CD27 on IgD- CD38dim B cell